Sodium Contents in Dairy Cow Urine and Soil Aggregate Sizes Influence the Amount of Nitrogen Lost from Soil - Toru Hamamoto; Yoshitaka Uchida (Applied and Environmental Soil Science)
Cow urine deposition on pasture soils is a major source of N-related environmental impacts in the dairy farming systems. The urine-N can potentially be lost to the ground water as nitrate (NO3-) and to the atmosphere as nitrous oxide (N2O). These N-related environmental impacts are possibly related to the sodium (Na+) concentrations in urine. We sampled a pasture soil and separated it into three aggregate size groups (0–3, 3–5, and 5–7 mm). Then, cow urine with variable Na+ concentrations (4.3–6.1 g Na+ L−1) was added to the soil cores. We treated the cores with simulated heavy rains and measured the amounts of calcium (Ca2+), Na+, potassium (K+), and inorganic-N leached from the soils. N2O emission rates were also determined throughout the experimental period. Increasing Na+ concentration in urine decreased the loss of NO3- (−20%), after repeatedly applied simulated rain treatments (30 mm × 3), whereas it increased the loss of ammonium (31%) and K+ (19%). For the loss of Ca2+ and the emissions of N2O, the effect of the Na+ concentrations was unclear. Field level studies and studies focusing on the mechanisms behind the changes in nutrient losses are needed.